A Maqasid Al-shariah Analysis Of Mandatory Pre-marital Screening For Stds And Fertility Among Malaysian Couples - Muhammad Adib Hafiz Adam; Muhammad Shazwan Sufian; Muhammad Razin Razali; Muhammad Aizat Mohamad Paisal; Mohd Harifadilah Rosidi (Research and Scientific Innovation Society (RSIS), 2025)
This study examines the necessity of implementing comprehensive pre-marital health screenings, including the detection of sexually transmitted diseases (STDs) beyond HIV and the assessment of fertility issues among prospective brides and grooms in Malaysia, through the lens of Maqasid al-Shariah. The background highlights that undiagnosed STDs and fertility disorders not only jeopardise individual health but also threaten the stability and sustainability of family institutions. Adopting a qualitative approach, this research conducts an in-depth literature analysis of classical Islamic jurisprudence, contemporary fiqh, and modern medical findings, with the Maqasid al-Shariah framework serving as the core analytical tool. The findings reveal that conditions such as syphilis, chlamydia, human papillomavirus (HPV), polycystic ovary syndrome (PCOS), and azoospermia can have significant implications for marital harmony, fertility outcomes, and even potential grounds for divorce. From a Shariah perspective, pre-marital screening is consistent with the objectives of preventing harm (darar) and safeguarding the public good, particularly in preserving life (hifz al-nafs) and lineage (hifz al-nasl). The study concludes that such screenings should be institutionalised through robust policy frameworks and strengthened public health education, ensuring that prevention strategies address medical necessities and Shariah imperatives. This research contributes to scholarly discourse on marital health governance and Islamic health policy in Malaysia, offering evidence-based justification for more inclusive and holistic pre-marital health screening practices.